Caracterização hidrogeológica de bacias hidrográficas do semiárido baiano através de técnicas de geoprocessamento - Silva, Edivam José da (2009)
For the adoption of water resources management in dry regions where water availability is limited, knowledge of the different processes of the hydrological cycle is needed, especially the precipitation and flow. Therefore, techniques of GIS are essential in studies of hydrological modeling. The study on maximum flow in a watershed is important because the same act on soil erosion, flooding in urban and rural areas, hydraulic works, among others. The Salitre basin is located in the State of Bahia, Brazil, and its Pacui sub-basin is fully inserted in the Campo Formoso municipio. With a drainage area of 987.74 km2, it is one of the main drainage sub-basin of Salitre river. Hence, the objective of this work was to characterize physiographically the Pacui sub-basin, estimate peak flow by USDA-SCS and Dooge methods, and estimate the hourly evapotranspiration in the sub-basin using the algorithm SEBAL (Surface Energy Balance Algorithms for Land) and images from Landsat 7 - ETM. The Global Mapper software was used for the analysis of land numerical model (SRTM). The ENVI 4.3 software was used for georeferencing of data from topographic maps of SUDENE, and the Arcmap 9.2 software was used for watershed delineation. The time of concentration was determined by USDA and Dooge methods. To determine the radiation balance images from the INPE (National Institute for Space Research) were used and processed by Arcmap ® software, within algorithm SEBAL was developed. The basin presented low slope and then tends to reduce the flood peak because of the low speed runoff. ArcHidro proved to be an effective tool in the delineation of river basins and the generation of drainage network and compared with those obtained by maps from SUDENE. The algorithm SEBAL proved to be an agile and efficient tool in evapotranspiration estimation. The use of SRTM provided information of parameters as surface albedo, incident long-wave and shortwave radiations, pixel to pixel. Lower rates of hourly evapotranspiration (<0.15 mm.h-1) were recorded in areas of exposed soils, and higher rates were found in irrigated areas and vegetation, expressing the sensitivity of algorithm SEBAL on evapotranspiration estimation in watershed scale.